Ensuring that offsets and other internationally transferred mitigation outcomes contribute effectively to limiting global warming. (23rd June 2021) - Allen, Myles; Tanaka, Katsumasa; Macey, Adrian; Cain, Michelle; Jenkins, Stuart; Lynch, John; Smith, Matthew
Abstract: Ensuring the environmental integrity of internationally transferred mitigation outcomes, whether through offset arrangements, a market mechanism or non-market approaches, is a priority for the implementation of Article 6 of the Paris Agreement. Any conventional transferred mitigation outcome, such as an offset agreement, that involves exchanging greenhouse gases with different lifetimes can increase global warming on some timescales. We show that a simple 'do no harm' principle regarding the choice of metrics to use in such transactions can be used to guard against this, noting that it may also be applicable in other contexts such as voluntary and compliance carbon markets. We also show that both approximate and exact 'warming equivalent' exchanges are possible, but present challenges of implementation in any conventional market. Warming-equivalent emissions may, however, be useful in formulating warming budgets in a two-basket approach to mitigation and in reporting contributions to warming in the context of the global stocktake.